2014
DOI: 10.1002/hipo.22348
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic impact of repeated stress on the hippocampal spatial map

Abstract: Stress alters the function of many physiological processes throughout the body, including in the brain. A neural circuit particularly vulnerable to the effects of stress is the hippocampus, a key component of the episodic and spatial memory system in both humans and rodents. Earlier studies have provided snapshots of morphological, molecular, physiological and behavioral changes in the hippocampus following either acute or repeated stress. However, the cumulative impact of repeated stress on in vivo hippocampa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 66 publications
2
23
0
Order By: Relevance
“…Research with rodents and nonhuman primates also demonstrates that exposure to an acute, uncontrollable stress impairs performance in cognitive and memory tasks that depend heavily on the PFC 90 . For example, restraint-stressed rats display impaired performance in a delayed spatial alternation task, a rodent behavioural test of spatial working memory 91 .…”
Section: Altered Cognition and Moodmentioning
confidence: 99%
“…Research with rodents and nonhuman primates also demonstrates that exposure to an acute, uncontrollable stress impairs performance in cognitive and memory tasks that depend heavily on the PFC 90 . For example, restraint-stressed rats display impaired performance in a delayed spatial alternation task, a rodent behavioural test of spatial working memory 91 .…”
Section: Altered Cognition and Moodmentioning
confidence: 99%
“…While some studies do not report altered neural excitability in association hippocampal dendritic atrophy produced by chronic stress [69, 73], other studies report increases in neural excitability [74]. The latter have informed a computational hippocampal network model in which dendritic atrophy produces increased excitability that impairs neuroplasticity by saturating long-term potentiation [75].…”
Section: Synaptic Deficits and Circuit Functionmentioning
confidence: 99%
“…The extent of chronic stress influences on place cells has just begun to be studied. A very recent study found that restraining mice 2 h/d for 5 consecutive days (but not 10 consecutive days due to adaptation) caused significant decreases in firing rates and field sizes of place cells 27 . However, this study focused exclusively on the place cell properties; whether the same stress affected other hippocampal functions, such as spatial learning and synaptic plasticity, are unknown.…”
mentioning
confidence: 99%